Drew Struzan : oeuvre - Struzan, Drew.; Struzan, Dylan; Struzan, Drew.; Titan Books (Firm) (London : Titan Books, 2011)
"Drew Struzan has created some of the most iconic movie posters of the last 30 years, including Raiders of the Lost Ark, Star Wars: The Empire Strikes Back, Harry Potter and the Sorcerer's Stone and Blade Runner. This hardcover edition, with a foreword by George Lucas, features over 250 pieces of artwork, including all of Drew's most iconic movie images, as well as other highlights from his career, including album, book and comic book covers, stamps, trading cards, promotional artwork and very personal original works. The book comes right up to date, including exclusive San Diego Comic-Con poster art produced for the Walking Dead television series (2010) and the Cowboys & Aliens movie (2011), with text by his wife Dylan"--Publisher's web site.
Foreword / by George Lucas -- Introduction -- Caveat -- Music -- Movies -- Publishing -- Commercial -- Personal -- Caption index -- Appendix : copyrights.
Companion volume to The art of Drew Struzan.
includes posters for A Muppet Christmas Carol, Adventures in Babysitting, Back to the Future, Coming to America, Cowboys and Aliens, Hellboy II, Indiana Jones, Kingdom of the Crystal Skulls, Raider's of the Lost Ark, Pan's Labyrinth, The Goonies, The Thing, and The Walking Dead.
Keywords: Struzan, Drew -- Themes, motives